Konsep Kedewasaan Usia Perkawinan dalam Masyarakat Sasak - Hamdi; Asri; Amil; Bimantoro, Imam Isnaeni (Juris Prima: Jurnal Inovasi Hukum dan Kebijakan, 2025)
Background: Marriage is a physical and spiritual bond between a man and a woman, establishing a happy and eternal household based on the principles of the Almighty God. According to Article 7, paragraph (1) of Law Number 16 of 2019, which amends Law Number 1 of 1974 concerning Marriage, marriage is only permitted when both the man and woman have reached the age of 19 years. In Indonesian society, marriages are typically conducted according to customary provisions that apply within the community. Purpose: This study aims to explain the concept of maturity in the context of marriage age within the Sasak tribe. Method: This research employs normative legal analysis, examining the application of positive legal principles through statue and conceptual approaches. Results: The concept of maturity in the Sasak community is rooted in religious understanding, particularly the concept of akil baligh, which refers to someone who has reached physical and mental maturity. At this point, they must adhere to Sharia law, known as mukallaf. In the Sasak culture, the concept of akil baligh translates into an individual's ability to think critically and take on responsibilities. For prospective brides, this means having the ability to weave, while for prospective grooms, it entails caring for two cows until they reach the age of 25. Conclusion and Recommendations: In alignment with the marriage age specified in Law Number 16 of 2019, Presidential Instruction Number 1 of 1991 regarding the Compilation of Islamic Law, and Regional Regulation of West Nusa Tenggara Province Number 5 of 2021 concerning the Prevention of Child Marriage, both prospective brides and grooms must be at least 19 years old. Further in-depth research is needed to examine the implementation and effectiveness of marriage age regulations in Indonesia, their impacts, and the challenges related to enforcement.